2020
DOI: 10.3390/nu12061589
|View full text |Cite
|
Sign up to set email alerts
|

Towards More Sustainable Diets—Attitudes, Opportunities and Barriers to Fostering Pulse Consumption in Polish Cities

Abstract: Despite the evidence-based health benefits of pulses and their significant role in sustainable diets, consumption remains at a very low level in highly developed countries. In an attempt to fill in the knowledge gaps on factors influencing this phenomenon, a study aimed at identifying attitudes, incentives and barriers to pulse consumption was carried out in a sample of 1027 Polish urban employees aged 25–40 years. The sample (quota type) was representative in terms of age and gender. Exploratory classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 53 publications
1
54
1
6
Order By: Relevance
“…Our study found that only 27% of respondents indicated the correct meaning of the term “sustainable food consumption”. However it must be noted that this result was higher than in other studies conducted in Poland among city dwellers [ 42 , 43 ]. In comparison the share of respondents who were familiar with this term in Polish rural households was only 9% [ 75 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Our study found that only 27% of respondents indicated the correct meaning of the term “sustainable food consumption”. However it must be noted that this result was higher than in other studies conducted in Poland among city dwellers [ 42 , 43 ]. In comparison the share of respondents who were familiar with this term in Polish rural households was only 9% [ 75 ].…”
Section: Discussioncontrasting
confidence: 72%
“…They could also give their own proposal. The correct response was deliberately simplified to “when everyday food consumption is carried out to minimize the impact on natural environment” like in our other surveys conducted among Polish city dwellers [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The perception of high-fiber foods such as pulses causing intestinal gas or discomfort after eating is a barrier cited in other studies [ 39 , 40 ]. Although a slight majority of the Midwestern college sample agreed that high fiber foods can cause gas, there was no difference by pulse type count groups.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pulse consumption among the Midwestern university students was associated with knowing how to prepare them, experience cooking dry pulses, and reporting a positive experience cooking pulses. Other studies have suggested that the most common reasons for not consuming pulses are general dislike or dislike of taste; a lack of familiarity, knowledge of recipes, and knowledge of preparation; and low interest [ 32 , 40 , 48 , 49 ]. Having the ability to prepare bean meals and considering them as tasty was associated with increased likelihood of bean consumption [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines for increasing the consumption of pulses are justified in terms of nutrition but also by socio-economic and environmental reasons. Cultivation of those plants is many times cheaper than meat production, especially in terms of water and soil efficiency, and it contributes to the reduction of greenhouse gas emissions [ 47 , 48 , 49 ]. Pulses have a significant impact on the reduction of hunger and malnutrition, ensuring food security and improving human health and the environment.…”
Section: Introductionmentioning
confidence: 99%